Ayurvedic Protocol in the Management of Bipolar Disorder with Psychotic Features in Young-Adult- Case Report (International Journal of Ayurveda and Pharma Research, 2023)
Bipolar Disorder (BD) is one of the world’s ten most disabling conditions taking away years of healthy functioning from individuals who have the illness. BD is a long-term, progressive psychiatric condition characterized by mood swings, including manic and depressive episodes. The prevalence rate is approximately 1% across all populations. Most of the complete aetiology or pathogenesis of BD is unknown. As per Ayurveda, Bipolar Disorder shows symptoms as mentioned in Unmada. In Unmada, there is considerable impairment in Ashtavibrama such as Manas, Buddhi, Samjnajnana, Smrti, Bhakti, Shila, Ceshta, as well as Acara. The present article deals with a diagnosed case of BD with psychotic features as per DSM 5 criteria, approached for an Ayurvedic management. A 20-year-old male presented in the hospital OPD with increased worries especially during evening hours, helplessness regarding his future, increased irritability, and sadness. On assessing Patient was an Avara Satwa. Management was planned with integrative approach comprising of Yukti vypasharaya and Satwawajaya. Internally he was given medicines to manage his depression and anxiety. He was advised with procedures namely Takrapana followed by Sodhananga snehapana, Sarvanga abhyanga and Bashpa sweda. Thereafter Virecana, and Yoga Vasti was given. During this time, he was also subjected to internal meditation and counselling techniques as well. The patient responded satisfactorily to the treatment and his symptoms improved significantly. There was marked reduction in his fear and pessimistic attitude. As an outcome, the care of BD using an integrative Ayurvedic approach proved effective.